Mengidentifikasi Kecerdasan Anak - Muhirdan, Muhirdan (Al-Riwayah : Jurnal Kependidikan, 2019)
This article aims to deliver the variety of intelligence that a child can possess also identifying children's intelligence so called multiple intelligence. The thing that lies behind this writing is a people belief that someone's success in the future is the fruit of his success in school today. A measure of one's success at school is his ranking or ability in answering all the questions tested at that time. But in fact it is not always true, that there are examples of people who are successful people who are dropped-out students. In this paper, it discusses the multiple intelligences presented by Howard which include 8 intelligences, namely: 1) Linguistic intelligence (word smart); 2) Spatial intelligence (picture smart); 3) Mathematical intelligence (logic smart); 4) Intelligence of kinesthesis (body smart); 5) Music intelligence (music smart); 6) Interpersonal intelligence (smart people); 7) Intrapersonal intelligence (self smart); 8) Naturalist intelligence (nature smart). A child's intelligence can be identified by a consultation and test for the child.